Determinant Factors of the Quality of Work of Life of Employees at the Horticulture and Plantation Food Crops Service of Merauke Regency - Bidang, Iriany; Noer, Elly; Pangaribuan, Nurmala (Technium Business and Management, 2024)
The performance assessment of the Merauke Regency Horticulture and Plantation Food Crops Service according to the government agency performance accountability system (SAKIP) in 2021 is still low, namely 69.87. Efforts need to be made to improve performance. This research highlights the quality of employees in dividing their time between work in the office and personal life. Improving the quality of employee work and life or Quality Work and Live (QWL) according to the initial survey is known to be possible by improving career development variables, work-life balance, employee attitudes, and compensation. This research aims to determine the determinant factors of QWL of employees at the Merauke Regency Horticulture and Plantation Food Crops Service. The research uses a descriptive quantitative method of hypothesis testing research over explanatory research because it is intended to explain the relationship of influence between variables through hypotheses. The research results show that work live balance (WLB) has a positive and insignificant effect on QWL, where increasing WLB can increase QWL. The more balanced work and life are, the higher the quality of work and life. Career development has a positive and insignificant effect on QWL. Smooth and fair career development will increase QWL. Meanwhile, office management's focus must be on variables with positive and significant results, where attitude has a positive and significant effect on QWL and compensation has a positive and significant effect on QWL. So efforts are needed to increase obedience and loyalty as part of the employee's attitude to the service as well as providing fair and transparent compensation.